2001
DOI: 10.1002/1521-3803(20010801)45:4<234::aid-food234>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Twin-screw extrusion of cassava starch and isolated soybean protein blends

Abstract: The effects of the extrusion parameters on isolated soybean protein (ISP) and cassava starch (CS) blends were studied. Extruded samples were prepared by using a ZSK-30 Werner and Pfleiderer twin-screw extruder. The study was carried out using Response Surface Methodology. The ISP followed by the moisture content were the most important linear variables significantly affecting axial expansion, specific volume, water solubility index and colour difference. The radial and axial expansion ranged from 2.30 to 3.77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Incorporation of WPC80 and CP increased WAI. Chang et al [37] described twin-screw processing of cassava starch and soy protein isolates, and reported decreased water absorption. Our results with cassava flour and WPC80 showed increased solubility and WAI, and decreased solubility for corn or barley blended with WPC80.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of WPC80 and CP increased WAI. Chang et al [37] described twin-screw processing of cassava starch and soy protein isolates, and reported decreased water absorption. Our results with cassava flour and WPC80 showed increased solubility and WAI, and decreased solubility for corn or barley blended with WPC80.…”
Section: Discussionmentioning
confidence: 99%
“…Extrusion process can affect the physicochemical and textural properties of starch–protein mixtures (Matthey and Hanna ; Chang et al . ; Ortiz et al . ; Zhu et al .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The extrusion behaviour of cassava for making snack foods was studied by some workers. [20][21][22][23][24] Earlier studies in our laboratory have shown that the nutritional and functional properties of cassava flour could be beneficially modified through pre-treatment with amylolytic enzymes as well as by blending with cereal and/or legume and bran sources. [18] The use of such modified composite flours for making baked goods having high protein and high dietary fiber has been also been investigated.…”
Section: Introductionmentioning
confidence: 99%